Correction to: Clitoral leiomyoma in a premenopausal woman: a case report - Gianmarco Taraschi; Diego Aguiar; Jean Christophe Tille; Patrick Petignat; Jasmine Abdulcadir (BMC Women's Health, 2020)
An amendment to this paper has been published and can be accessed via the original article.